Assessment of Groundwater Quality in the Talensi District, Northern Ghana - Larry Pax Chegbeleh; Bismark Awinbire Akurugu; Sandow Mark Yidana (The Scientific World Journal)
A comprehensive chemical quality assessment of groundwater resources in the Talensi District has been conducted using conventional graphical methods and multivariate statistical techniques. The study sought to determine the main controls of groundwater chemistry and its suitability for domestic and irrigation purposes in the district. Silicate and carbonate mineral weathering were identified as the main controls on groundwater chemistry in the district, with reverse ion exchange also playing a role. High nitrate and lead levels observed have been associated with agrochemicals and wastewater from farms and homes. Three main flow regimes have been identified with Q-mode cluster analysis, in which mixed cation water types have been revealed, where areas designated as recharge zones are dominated by Na+ + K+–Mg2+–HCO3− fresh water types characterised by low mineralisation and pH, which evolve into Mg2+– Na+ + K+– HCO3− fresh water type with corresponding increased mineralisation of the groundwater. Based on the water quality index (WQI) technique modified for the district and an interpolation technique using ordinary kriging developed from a well-fitted exponential semivariogram for the estimated WQIs, the groundwater quality has been spatially classified as generally ‘good’ to ‘excellent’ for domestic purposes. Generally, the quality of groundwater for domestic usage deteriorates as one moves towards the north of the district, whereas waters in the east and west present the best quality. Classifications based on the United States Salinity Laboratory (USSL), Wilcox, and Doneen diagrams suggest that groundwater from the unconfined aquifers of the district is of excellent quality for irrigation purposes.